(untitled) - Ms. C. Rajeswari, Dr. N. Gejeswari (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Shobha De is a staunch feminist and rebel to some extent. A typical Indian feminist novel records the suffering of urban middle class women in the patriarchal setup. This type of novel generally includes growth of a girl in the Indian middle class family with her male siblings to focus on gender discrimination; later on it focuses on the challenges of her married life where she is unheard, neglected and suppressed. And finally this suppressed volcano of woman protagonist results into liberty, self-respect and struggle for self-identity. Women writers like Shashi Deshpande, Arundhati Roy, Anita Desai, Shobha De in India have changed traditional picture of enduring, self-sacrificing women with new bold and liberated urban female characters in their fiction.